The Eastern Caribbean Central Bank : Challenges to an Effective Lender of Last Resort - Druck, Pablo; Dehesa, Mario (Washington, D.C. : International Monetary Fund, 2008)
The paper analyzes the challenges for the Eastern Caribbean Central Bank (ECCB) to be an effective lender of last resort (LOLR) as part of a modern banking crisis resolution framework. The main results from the theoretical model of the ECCB's institutional arrangement are that the majority of currency union members may veto emergency lending in the case of a member-specific shock, as such lending may endanger the stability of the currency board (by lowering the central bank's international reserves, thus raising devaluation risk). However, in the presence of contagion across countries, all currency union members have a vested interest in liquidity supply from the central bank. A key policy recommendation is that currency union members need a stronger fiscal position to continue to access international financial markets and sustain the exchange rate peg.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet